Morphological Identification Characteristics of Basil (Ocimum spp.) in Tabanan Regency, Bali, Indonesia - Harianja, Shara Yulita; Sudiarta, I Putu; Zhao, Tiejun (International Journal of Biosciences and Biotechnology, 2024)
Basil (Ocimum spp.) is an aromatic plant and is the wealthiest essential oil-producing genera from the Lamiaceae family. Due to the various phytochemical compounds or secondary metabolites, Basil has the potential of medicinal plant germplasm as a source of biopharmaceuticals. Several types of Basil grow in Bali, especially in Tabanan Regency, but their morphological characteristics have yet to be identified. This study aims to identify the morphological characteristics of the four types of Basil found growing at that location: Kecarum, Selasih, Tulasi, and Ruku-ruku. This research was conducted by characterizing the characteristics of the parts of the basil plant, including the morphology of the crown (Botany), stem (Caulis), flowers (Flos), leaves (Folium), and fruit (Fructus). The results of the characterization showed that there were similarities between the four types of Basil and differences in crown shape, plant height, the direction of branch growth, type of branching, leaf shape, color (leaves, stems, flowers, fruit), leaf tips, and leaf layout. , and the base of the leaf. Based on the morphological identification, Kecarum and Selasih have similar morphology to Ocimum americanum L and Ocimum basillicum. Tulasi and Ruku-ruku are morphologically identical to Ocimum sanctum var. Rama (red holy basils) and Ocimum campechianum. Keywords: Biopharmaceuticals, Basil, Lamiaceae, Morphology, Ocimum spp.